The Study of Local Community Participation of Ecotourism Development in Daming Mountain Nature Reserve in Nanning, Guangxi, China - Yi-sha, Ma; Cheablam, Onanong (Science, Technology, and Social Sciences Procedia, 2021)
Community participation is one of the main content of ecotourism development. In order to further understand the degree of residents’ participation in ecotourism development in Daming Mountain Nature Reserve, this paper selected 6 villages, which have the closest relations in the process of ecotourism development in Daming Mountain Nature Reserve, as the research object. It adopted the way of questionnaire and interviews to investigate. The questionnaire was conducted by random sampling, one-to-one question-and-answer, and was filled in by the investigator himself. Interview is a random question and answer among respondents in the process of questionnaire, and further in-depth investigation of residents. The results show that the current ecotourism development in this area has not well connected the tourism development with the economic interests of local residents, nor has it driven the development of local economy and environmental improvement, resulting in the local residents’ dissatisfaction with the current situation of ecotourism development in Daming Mountain Nature Reserve, affecting the degree of community participation in ecotourism. At the same time, it can also be seen that the local community has a strong subjective desire to participate in the development of ecological tourism. In view of the existing problems, this paper puts forward the corresponding countermeasures for local residents to participate in ecotourism development and realize sustainable development of ecotourism in this area.